A STUDY OF CHARACTER DEVELOPMENT: SOCIAL IMPACT IN DANNY SANTIAGO’S NOVEL ENTITLED FAMOUS ALL OVER TOWN - Saputro, Ahmad Alfiantoro (LANTERN (Journal on English Language, Culture and Literature), 2016)
Social Impact is a key to the harsh life of Mexico-Americans society in novel Famous All Over Town by Danny Santiago. The purpose of the research is to discuss characters development through harsh life of Mexican-American society in Los Angles. The writer used intrinsic theories such as character and setting in conducting this research. The writer also usedBibb Latané’sdynamic social impact theory in this research. The resultofthis researchis to provethatsocial influencesgreatlyaffect the development ofcharacterbehavior. Chatoisactuallyagoodkidbecauseenvironmentalfactorsturn out to bemischievous. The situation in a society may extremely influential to the psychological development.